Mediating role of employee engagement between Blue Ocean Leadership and team performance - Zi Jian Oh; Yin Yin Khoo; Marinah Awang (International Journal of Evaluation and Research in Education (IJERE), 2022)
The study examined the mediating effect of employee engagement between blue ocean leadership and team performance among lecturers. A cross-sectional study design was used, and quantitative data were collected using a structured survey from 2,580 lecturers from the population across the 22 vocational colleges in Malaysia's north zone. Structural Equation Modeling (SEM) was used for data analysis. The results revealed a considerable positive relationship between blue ocean leadership and employee engagement, as well as between employee engagement and team performance. Employee engagement, as demonstrated through the use of bootstrapping analysis, acts as a mediator between blue ocean leadership and team performance. The finding supported the Blue Ocean Leadership theory and Social Exchange theory in this study. Future research is be recommended to conduct in other states as well as private institutions to get a comprehensive understanding.